(untitled) (Italian Journal of Public Health, 2010)
Background: The “Valentino” cross-sectional study is aimed at evaluating the prevalence and pattern of cigarette smoking according to occupational group in a representative sample of workers aged 18-35 years from Abruzzo, Italy. Methods: Randomly selected workers anonymously self-compiled a structured questionnaire containing validated items. Job type was coded according to the International Standard Classification of Occupations. Results: The sample consisted of 3989 workers. Current smoking prevalence was 45.9%, varying across occupational groups and ranged from 37.2% among clerical support workers, up to 57.1% among craft, agricultural and fishery sector workers. After controlling for several potential confounders using logistic regression, craft, agricultural, forestry and fishery workers (adjusted odds ratio 1.65; 95% confidence intervals 1.21-2.27), and call-center operators (1.91; 1.44-2.53) were significantly more likely to be current smokers than professionals and clerical or support workers. Interestingly, when alcohol and cannabis use were included in multivariate analysis, the association between smoking and gender was no longer significant. Conclusions: An independent association was found between specific occupational classes and tobacco smoking, suggesting occupation type should be considered in prioritizing subsets of populations towards which smoking cessation campaigns should be targeted first.